Examining the interplay of brand satisfaction, trust, and loyalty among BSI mobile users: The mediating role of brand attachment - Dahmiri, Dahmiri; Khalik, Idham; Bhayangkari, Sylvia Kartika Wulan; Syafri, Rista Aldilla (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2023)
This study investigates the effects of brand satisfaction, trust, and loyalty among Bank Syariah Indonesia (BSI) mobile phone users. Additionally, it delineates the mediating role of brand attachment on a collective and individual scale. The study utilizes a sample drawn from diverse BSI customer bases across Indonesia. Data was gathered through structured questionnaires disseminated via WhatsApp, Facebook, and email, facilitated by Google Forms. The research adopted a quantitative methodology, incorporating statistical and hypothesis tests, with preliminary evaluations involving validity, reliability, and normality tests. Data analysis encompassed qualitative and quantitative methodologies, employing Structural Equation Modeling (SEM) for the quantitative segment. This pioneering research in Indonesia scrutinizes the interrelations between brand satisfaction, brand trust, and brand loyalty, specifically in the context of BSI mobile phone users, offering potential insights that might be pivotal for augmenting BSI's clientele. The findings demonstrate that the model's Goodness of Fit index meets the requisite criteria, illustrating the analytical competence of the model. Identifying service quality, marketing mix, and brand image as significant determinants influencing customer satisfaction is noteworthy. Furthermore, the research unveils that brand satisfaction, trust, and attachment are instrumental in shaping brand loyalty among BSI mobile users. Distinctively, brand satisfaction exerts an indirect influence on brand loyalty mediated by brand attachment, paralleled by a similar indirect influence of brand trust on brand loyalty through brand attachment. Incorporating brand attachment as a mediating variable in this study augments the comprehension of the interplay between these elements, yielding more substantial conclusions about their impact on brand loyalty.